2018
DOI: 10.1177/2047487318755531
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose co-transporter 2 inhibitors and cardiovascular outcomes: A systematic review and meta-analysis

Abstract: Background The risks and benefits of sodium-glucose co-transporter 2 (SGLT2) inhibitors on cardiovascular outcomes have not been well established. We pooled evidence from all available clinical trials to assess the cardiovascular effects of this drug. Design A systematic review and meta-analysis of randomised controlled trials. Methods We queried electronic databases (MEDLINE, Scopus, CENTRAL and clinicaltrials.gov) from their inception to July 2017 for published and unpublished placebo controlled trials of SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 25 publications
4
77
0
10
Order By: Relevance
“…[161][162][163][164] Newer glucose-lowering drugs have been evaluated in large-scale trials, but, in most cases, these investigations did not systematically identify AF events and hence the number of captured AF events was too small to allow for meaningful analysis. 165 Nevertheless, it is noteworthy that the risk for AF appears to be numerically reduced by sodium-glucose cotransporter 2 inhibitors, 166 which are known to reduce the mass and inflammation of epicardial adipose tissue [167][168][169][170] and which have been shown to decrease the incidence of HF events, including those caused by HFpEF. 4…”
Section: Metformin and Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…[161][162][163][164] Newer glucose-lowering drugs have been evaluated in large-scale trials, but, in most cases, these investigations did not systematically identify AF events and hence the number of captured AF events was too small to allow for meaningful analysis. 165 Nevertheless, it is noteworthy that the risk for AF appears to be numerically reduced by sodium-glucose cotransporter 2 inhibitors, 166 which are known to reduce the mass and inflammation of epicardial adipose tissue [167][168][169][170] and which have been shown to decrease the incidence of HF events, including those caused by HFpEF. 4…”
Section: Metformin and Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…In absolute terms the benefits reduced CHD events more modestly than blood pressure lowering or low density lipoprotein cholesterol (LDL‐C) reduction. More recently several trials of sodium glucose co‐transporter 2 (SGLT2) inhibitors and glucagon‐like peptide 1 (GLP‐1) agonist have shown significant reductions in cardiovascular events despite achieving about only 1/3 of the difference in HbA1c as earlier studies . In contrast, trials with DDP4 inhibitors which achieved similar reductions in HbA1c have failed to show any cardiovascular benefits .…”
Section: Reducing Cardiovascular Outcomes In Diabetesmentioning
confidence: 99%
“…More recently several trials of sodium glucose cotransporter 2 (SGLT2) inhibitors and glucagon-like peptide 1 (GLP-1) agonist have shown significant reductions in cardiovascular events despite achieving about only 1/3 of the difference in HbA1c as earlier studies. 30,31 In contrast, trials with DDP4 inhibitors which achieved similar reductions in HbA1c have failed to show any cardiovascular benefits. 32 Taken together these data suggest that it matters how you reduce HbA1c with GLP-1 agonists and SGLT2 inhibitors offering benefits beyond the magnitude of glucose reduction and may be related to pleiotropic effects of these therapies.…”
Section: Treatment Of Dysglycaemiamentioning
confidence: 99%
“…However, these trials were not designed to detect an effect on singular endpoints . Later meta‐analyses and real‐world studies involving up to 400 000 patients using SGLT2 inhibitors showed a significant reduction in the rate of myocardial infarction, stroke, heart failure and CV death . Several hypotheses have been formulated to explain these marked cardioprotective effects .…”
Section: Introductionmentioning
confidence: 99%